Serum lipids and suicidal risk among patients with schizophrenia spectrum disorders: Systematic review and meta‐analysis. (26th May 2021) - Sankaranarayanan, Anoop; Pratt, Robin; Anoop, Aparna; Smith, Angela; Espinoza, David; Ramachandran, Padmavati; Tirupati, Srinivasan
Abstract: Objective: A systematic review of literature was conducted to determine the association between serum lipids and suicidality in people with schizophrenia spectrum disorders. Methods: We undertook a systematic search of multiple databases for studies that ascertained an association between serum lipids and suicidality in adult patients with schizophrenia spectrum disorders (18–65 years) from database inception to 2 September 2020. Qualitative analysis was done using National Institute of Health (NIH) scales. The standard mean difference (SMD) and 95% confidence intervals (CI) were calculated for each study and standardized relative to the study. Adjusted p ‐value, Z‐test, and heterogeneity were calculated, as well as testing for publication bias. Results: Of 1262 records identified, 17 studies ( n = 3113) were included in our systematic review, while 11 studies were included in the meta‐analysis. The majority of studies (11) rated fair on qualitative analysis. Data from seven studies ( n = 1597) revealed a medium effect size for an association between low total cholesterol and suicide attempts (SMD −0.560; 95% CI: 0.949–0.170; p = 0.005). People with history of suicide attempt had a mean cholesterol value 0.56 SD lower than the mean in those without suicide attempts. There were differences in how a suicide attempt was defined and there was high heterogeneity ( I 2 = 83.3%). No significant association was found between any of the serum lipid parameters and suicide ideation. Funnel‐plot analysis suggested small study effects with publication bias. Conclusions: Suicide attempts in people with schizophrenia spectrum disorders are associated with low mean total cholesterol levels.